2013
DOI: 10.1088/0953-8984/25/23/236003
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-glass magnetic state in R5Pd2(R = Ho, Tb) compounds evidenced by AC-susceptibility and neutron scattering measurements

Abstract: AC- and DC-susceptibility, high-field magnetization and neutron diffraction measurements have been performed in order to study the magnetic state of R5Pd2 (R = Ho, Tb) compounds. The results show that both compounds undergo cluster-glass freezing upon cooling below Tf. According to the neutron diffraction a long-range magnetic order is absent down to 2 K and magnetic clusters with short-range incommensurate antiferromagnetic correlations exist not only below Tf but also in a wide temperature range above the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
8
19
0
Order By: Relevance
“…in the temperature range of measurement. These results also supported the presence of glasslike behaviour in these compounds which were also in accordance to the results obtained for other R 5 Pd 2 members [14,[19][20].…”
Section: Magnetic and Mce Studies On Dy 5 Pd 2-x Ni X (X = 0 And 1)supporting
confidence: 91%
See 1 more Smart Citation
“…in the temperature range of measurement. These results also supported the presence of glasslike behaviour in these compounds which were also in accordance to the results obtained for other R 5 Pd 2 members [14,[19][20].…”
Section: Magnetic and Mce Studies On Dy 5 Pd 2-x Ni X (X = 0 And 1)supporting
confidence: 91%
“…In order to further understand the magnetic nature of compound, magnetic isotherms as a function of applied field (in the range ±70 kOe) at different temperatures (2-100 K) were measured and the resulting curves are shown in Figure 2 whereas the presence of later property is an indication of the existence of ferromagnetic component, implying that multiple interactions were present in these compounds. Similar behaviour had also been reported in literature for other compounds [20]. Additionally coercive field was found to decrease exponentially with increasing the temperature for both the compounds (lower inset Figure 2(b)).…”
Section: Magnetic and Mce Studies On Dy 5 Pd 2-x Ni X (X = 0 And 1)supporting
confidence: 90%
“…The value of η falls into the range of 4–12 for spin glasses31323336404445, which is not cluster-glass like character46. is close to 7.9, the calculated value for the three-dimensional Ising spin-glass4748.…”
Section: Resultssupporting
confidence: 53%
“…This group of spins along with strong anisotropy of Er ions on application of magnetic field can make the system highly irreversible and can lead to deviation from A-T line [29]. For R 5 Pd 2 , p is seen to be different for different members of the family [14], as different rare-earths show different anisotropic behaviour in the applied magnetic field [29]. But, as reported by Wegner and Mydosh [30], such A-T phase boundary cannot be considered as an exact proof of glass-like phase transition.…”
Section: Magnetization Studymentioning
confidence: 99%
“…Hence these compounds can be categorized to the family 3 where origin of glassy behaviour is not due to geometrical frustration or structural disorder. Klimczak et al, reported that the compound Er 5 Pd 2 orders magnetically and shows spin reorientation [17] whereas Gubkin et al, suggested that the members of R 5 Pd 2 family may have a glassy magnetic state at low temperature [14]. However, a detailed study about the compound Er 5 Pd 2 is lacking in literature.…”
Section: Introductionmentioning
confidence: 99%